MIFTAHUL JANNAH CAHAYA RAMADAN ORPHANAGE: TOGETHER REACHING BLESSINGS - Falahuddin; Arliansyah; Fuadi; Yulis Terfiadi; Erna Isfayanni; Frengki Putra Ramansyah (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
This article examines the Ramadan community-service program entitled Miftahul Jannah Cahaya Ramadan Orphanage: Together Reaching Blessings as a child-centered social initiative that integrates spiritual education, psychosocial support, Islamic philanthropy, and collaborative volunteerism. The program was designed to create a joyful, dignified, and educational Ramadan experience for children living in orphanage care while strengthening partnerships between caregivers, volunteers, donors, and local communities. A descriptive community-service approach was used through needs assessment, program planning, implementation, observation, reflection, and follow-up recommendation. The findings indicate that Ramadan service activities can support children’s emotional well-being, social connectedness, religious literacy, and sense of recognition when they are organized through ethical communication, participatory engagement, and sustainable partnership. The study also shows that charity-based Ramadan programs should move beyond one-time donation delivery toward relational care, educational enrichment, and accountable community collaboration. The article contributes a practical model for orphanage-based Ramadan service that places children’s dignity, happiness, and development at the center of Islamic social responsibility.